Depth Oriented Brief Therapy: An Ideal Technique as Hospice Lengths-of-Stay Continue to Shorten - Thomson, Judith E. (Journal of pastoral care & counseling, 2002)
The authors note that as hospice patients' lengths-of-stay continue to shorten, psychosocial/spiritual counselors are being challenged to help patients and families process the myriad of issues terminal illness gives rise to. Given this reality, the authors suggest that the Depth Oriented Brief Therapy (DOBT) approach should prove especially useful. The DOBT premise is that if people can be helped to experience the emotional meanings of why they hold on to emotionally painful symptoms then they can abandon their symptoms for healthier ways of being.